Bioinspired Energy Conversion in Nanofluidics: A Paradigm of Material Evolution. Issue 45 (10th August 2017) - Feng, Yaping; Zhu, Weiwei; Guo, Wei; Jiang, Lei
Abstract: Well‐developed structure–function relationships in living systems have become inspirations for the design and application of innovative materials. Building artificial nanofluidic systems for energy conversion undergoes three essential steps of structural and functional development with the uptake of separate biological inspirations. This research field started from the mimicking of the bioelectric function of electric eels, wherein a transmembrane ion concentration gradient is converted into ultrastrong electrical impulses via membrane‐protein‐regulated ion transport. On a small scale, solid‐state nanopores are transformed from cylindrical to cone‐shaped to acquire asymmetric ion‐transport properties; they also further gain versatile responsiveness via chemical modification. These features mimic the rectifying and gating functions of the biological ion channels. Toward large‐scale integration and real‐world applications, the structure of the nanofluidic system evolves from a one‐dimensional straight‐channel to a two‐dimensional layered membrane, inspired by the layered microstructure of nacre. The research progress, current challenges, and future perspectives of this growing field are highlighted and discussed from the viewpoint of material evolution. Abstract : Building artificial nanofluidic systems for energy conversion started from the mimicking of the bioelectric function of electric eels. Nanofluidic devices have undergone three essential steps of structural and functional development with the influence of separate biological inspirations. Recent progress, challenges, and future perspectives are highlighted and discussed from the viewpoint of material evolution.